2007
DOI: 10.1590/s0034-72992007000600005
|View full text |Cite
|
Sign up to set email alerts
|

Processo de adaptação de próteses auditivas em usuários atendidos em uma instituição pública federal - parte I: resultados e implicações com o uso da amplificação

Abstract: Heari ng aid fitting involves numerous issues that must be investigated -from the device supply all the way to results achieved with it in order to improve its results in planning Auditory Health Care. Aims: to verify difficulties related to device use, batteries and ear molds handling, the very characteristics of sound amplification, and to discuss factors that impact audiological rehabilitation in this group of patients. Materials and Methods: 31 individuals, from 12 to 77 years age, with bilaterally symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 3 publications
3
14
1
14
Order By: Relevance
“…Complaints about difficulties in adapting to hearing aids, similar to those reported by most people in this study that were not using the device, such as discomfort with the amplification caused by noise, headache, pruritus, among others, were also mentioned in another study (26) and require adequate monitoring by the health service to be investigated and remedied.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Complaints about difficulties in adapting to hearing aids, similar to those reported by most people in this study that were not using the device, such as discomfort with the amplification caused by noise, headache, pruritus, among others, were also mentioned in another study (26) and require adequate monitoring by the health service to be investigated and remedied.…”
Section: Discussionsupporting
confidence: 68%
“…While for some the device has been representing a significant improvement in their quality of life, for others the impact has not been observed in a significant way. References to defects in the device, or difficulties in obtaining the battery, by access inability or financial matters, indicated by some patients in the present study as reasons for not making use of hearing aids, can be based on the fact that, despite having auditory rehabilitation guaranteed by the Unified Health System, there are monetary costs involved in the maintenance of the appliance, which are the responsibility of the patient, which could explain the delay in seeking resolution to the problems encountered (26) . Even among those who were making use of hearing aids, some users reported that they do not use it full time to "save" the batteries.…”
Section: Discussionmentioning
confidence: 90%
“…Assim, em todos os casos o acompanhamento é imprescindível, pois a orientação e o acompanhamento são a chave do sucesso do uso efetivo do aparelho auditivo, não devendo, portanto, ser minimizada a sua importância no processo de adaptação 5,26,27 .…”
Section: Figura 5 -Distribuição Quanto à Limitação Residual Nas Ativiunclassified
“…De acordo com as estratégias desta nova política, o processo de reabilitação audiológica passa a envolver um trabalho muito mais amplo que prevê a adaptação de AASI de fluxo contínuo, com acompanhamento médico e fonoaudiológico, tanto para ajustes como para verificações periódicas das condições técnicas e do benefício obtido com o uso desses equipamentos, e quando necessário de terapia fonoaudiológica, além de assistência social e psicológica (23).…”
Section: Discussionunclassified